2013
DOI: 10.1103/physrevb.88.104107
|View full text |Cite
|
Sign up to set email alerts
|

Phonon spectrum, thermodynamic properties, and pressure-temperature phase diagram of uranium dioxide

Abstract: We present a study of the structural phase transition and the mechanical and thermodynamic properties of UO2 by means of the local density approximation (LDA)+U approach. A phase transition pressure of 40 GPa is obtained from theory at 0 K, and agrees well with the experimental value of 42 GPa. The pressure-induced enhancements of elastic constants, elastic moduli, elastic wave velocities, and Debye temperature of the ground-state fluorite phase are predicted. The phonon spectra of both the ground state fluori… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
78
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 67 publications
9
78
0
Order By: Relevance
“…While recent first-principles simulations for UO 2 [3][4][5] have reported good agreement with experimental elastic constants, bulk moduli, and lattice heat capacity measurements, a reduced level of agreement was found for phonon dispersion and phonon density of states (PDOS) simulations compared to the experimental inelastic neutron scattering (INS) results of Dolling et al [6]. Moreover, Pang et al [2] reported results similar to other ab initio phonon dispersion simulations [2][3][4][5], but differences of more than a factor of two between ab initio simulations and INS measurements of phonon linewidths (i.e., inverse lifetimes) for UO 2 [2], especially at high temperature (1200 K).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While recent first-principles simulations for UO 2 [3][4][5] have reported good agreement with experimental elastic constants, bulk moduli, and lattice heat capacity measurements, a reduced level of agreement was found for phonon dispersion and phonon density of states (PDOS) simulations compared to the experimental inelastic neutron scattering (INS) results of Dolling et al [6]. Moreover, Pang et al [2] reported results similar to other ab initio phonon dispersion simulations [2][3][4][5], but differences of more than a factor of two between ab initio simulations and INS measurements of phonon linewidths (i.e., inverse lifetimes) for UO 2 [2], especially at high temperature (1200 K).…”
Section: Introductionmentioning
confidence: 99%
“…Counterintuitively, however, the major source of the discrepancy in the phonon linewidth simulations was identified [2] to lie within the phonon energies and dispersion. This suggests that the presently available ab initio simulations [3][4][5] of the second-order interatomic forces are not sufficiently accurate for handling anharmonicity and phonon linewidths, and hence, for simulations of thermal transport in UO 2 . Considering the large anharmonicity of UO 2 and the limitations of the quasiharmonic approximation to account for temperature effects as used in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…We chose U = 6.0 eV and J = 0.6 eV in our calculations, in accord with the previous DFT + DMFT calculations [16]. For the double counting term, we used the fully localized limit scheme [30], which is commonly used in DFT + U or DFT + DMFT calculations for correlated insulators [9][10][11][12][13]. All of the calculations were carried out at the inverse temperature β = 100 eV −1 (T ≈ 116 K), which is much higher than the experimental Néel temperature (T N = 30.8 K) [2].…”
mentioning
confidence: 99%
“…The ground state of UO 2 is an antiferromagnetic Mott insulator with a sizeable band gap of ∼2.1 eV [8]. To study the electronic structure of UO 2 , many traditional first-principles approaches have been employed, such as the local density approximation (LDA) (or generalized gradient approximation (GGA)) plus Hubbard U approach [9][10][11][12][13], the hybrid functional method [14], and the self-interaction corrected local spin-density approximation (SIC-LSDA) [15]. However, none of the above methods can provide a satisfactory description of UO 2 over a wide range of conditions.…”
mentioning
confidence: 99%
“…At ambient pressure it is a Mott insulator and crystallizes in a cubic fluorite structure. Given the importance of this material, its electronic structure and energetics have been extensively investigated both experimentally and theoretically, e.g., with DFT+U [30][31][32] and other single-particle approaches [33,34]. However, within these techniques it is not possible to address the properties of the paramagnetic state of this material, which is stable above the Néel temperature T N 30.8 K [35].…”
mentioning
confidence: 99%